Maritime law - Baatz, Yvonne (Routledge c 2014, 2014)
Maritime Law is written by a team of leading academics and practitioners, each expert in their own field. Together, they provide clear, concise and fully up-to-date coverage of topics ranging from bills of lading to arrest of ships, all written in an accessible and engaging style. As English law is heavily relied on throughout the maritime world, this book is grounded in English law whilst continuing to analyse the key international conventions currently in force